1984
DOI: 10.1111/j.1471-0528.1984.tb05890.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vasoactive autacoids on the human umbilical‐fetal placental vasculature

Abstract: summary Studies have been made of the effects of autacoids on vascular tone of the human perfused fetal umbilical vein and placental lobule. The thromboxane A2 (TxA2)‐mimetic substance U46619, 5‐hydroxytryptamine and bradykinin were powerful constrictors of the vein. Prostaglandins E2 (PGE2), F2α(PGF2α), adrenaline, noradrenaline, histamine and angiotensin II were much less potent. Venoconstriction caused by U46619, bradykinin and 5‐hydroxytryptamine was reduced during inhibition of phospholipase A2 with mepac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 26 publications
3
46
1
Order By: Relevance
“…Koren et al (1966) have shown that the 5-HT content of the placenta gradually increases as pregnancy advances; this is consistent with the lack of 5-HT immunoreactivity in endothelial cells from early pregnancy observed in this study. Various authors have demonstrated that placental vessels are much less sensitive to 5-HT than umbilical arteries (Panigel 1962;Mak et al 1984;MacLean et al 1992); this implies that the main role for 5-HT lies in the umbilical vessels. Responses to 5-HT in the feto-placental circulation have been demonstrated by several authors (McGrath et al 1990;Breslin 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Koren et al (1966) have shown that the 5-HT content of the placenta gradually increases as pregnancy advances; this is consistent with the lack of 5-HT immunoreactivity in endothelial cells from early pregnancy observed in this study. Various authors have demonstrated that placental vessels are much less sensitive to 5-HT than umbilical arteries (Panigel 1962;Mak et al 1984;MacLean et al 1992); this implies that the main role for 5-HT lies in the umbilical vessels. Responses to 5-HT in the feto-placental circulation have been demonstrated by several authors (McGrath et al 1990;Breslin 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Maximal activation of TxAz receptors in the human placental fetal vasculature with the TxAz-mimetic U466 19 can cause complete occlusion of the fetal circulation, emphasizing the adverse effects this autacoid can have on blood flow when liberated in excessive amounts during disease. Similar degrees of maximal vasoconstriction can also be caused by high concentrations of PGFzn and PGEz, although these autacoids are approximately I00 and 3000 times, respectively, less potent than U46619 (Mak et al 1984). Prostacyclin, the physiological antagonist of TxAz, has also been indirectly identified as its stable metabolic product 6-ketoPGF1,.…”
Section: Effects Of Passage Through the Placenta On The Activities Ofmentioning
confidence: 99%
“…or inhaled 70% N20 and 30% 02. These drugs have no apparent effects on responses of the foetal vascular tissues under the conditions used (Mak et al, 1984 tration causing a threshold effect, the concentration was increased by approximately 0.5 log10 intervals, after each effect obtained became constant. The highest concentration used was either that causing a maximal response or that which could be achieved due to the constraint of lack of sufficient solubility in the solution being infused.…”
Section: Collection Ofplacentaementioning
confidence: 99%